(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This paper examines Article 358 of the Criminal Procedure Code of the Republic of Uzbekistan, which regulates the procedure for appealing actions and decisions of investigators and prosecutors. The study analyzes the normative content of this provision in conjunction with other procedural norms of the CPC, constitutional guarantees of judicial protection, and relevant international human rights standards. Special attention is paid to the dual mechanism of administrative (prosecutorial) and judicial review, its legal nature, functional limitations, and practical implications for the protection of individual rights. The author argues that the existing model, while formally consistent with international requirements, requires further development to ensure effective remedies and genuine judicial control at the pre-trial stage.